Empowering Sufferers, Families, and Health Cadres To Understand Hypertension and Its Treatment Through Integrated Socialization (JURNAL PENGMAS KESTRA (JPK), 2025)
Hypertension is a serious health problem in communities worldwide. Patients' non-compliance with hypertension management will negatively impact their health. Partner communities who are less compliant with hypertension management and limited accessibility of promotive-preventive services can exacerbate hypertension in their partner communities. This community service aims to improve the capacity for holistic hypertension management at the patient, family, and community levels by strengthening the understanding of patients, families, and health cadres. The activity was implemented through integrated socialization (interactive lectures) and demonstrations of complementary therapy exercises. Educational materials included hypertension management emphasizing the prevention of complications, how to monitor signs and symptoms of hypertension, management, and the importance of the role of families and health cadres in psychological support for patients and their families, routine check-ups, diet, and regular medication administration. At the end of the implementation phase, the team demonstrated brisk walking exercises. Evaluation of the activity was conducted before and after the presentation of the activity material and observation of independent practice of the exercises that had been delivered. The evaluation results showed a difference in the average pre- and post-test scores. The average pre-test score was 14.45, while the average post-test score was 18.3. Further analysis showed an increase in the average score, namely 3.85. The community service program successfully increased the participants' understanding of hypertension management. This understanding is crucial for controlling hypertension mortality and morbidity.